2013
DOI: 10.1149/ma2013-02/15/1376
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Durability and Performance of a Proton Exchange Membrane Electrode Assembly Used in the Separation of Hydrogen From Helium

Michael Angelo,
Keith Bethune,
Richard Rocheleau

Abstract: not Available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…For example, Abdulla et al considered H 2 recovery from a reformate mixture using a H 2 pump and summarized several additional uses including the work of Rohland et al for H 2 compression, Barbir and Gorgun for H 2 recirculation in fuel cell stacks, Sedlak et al for H 2 purification for mixed streams with specific examples cited for H 2 purification with carbon dioxide (CO 2 ) by Gardner and Ternan, and nitrogen (N 2 ) by Casati et al (1)(2)(3)(4)(5)(6). Recently, Angelo et al have demonstrated that a H 2 pump can be used to purify inert gases where H 2 was successfully separated from inert Helium (He) using a proton exchange membrane fuel cell system (PEMFCS) (7,8).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, Abdulla et al considered H 2 recovery from a reformate mixture using a H 2 pump and summarized several additional uses including the work of Rohland et al for H 2 compression, Barbir and Gorgun for H 2 recirculation in fuel cell stacks, Sedlak et al for H 2 purification for mixed streams with specific examples cited for H 2 purification with carbon dioxide (CO 2 ) by Gardner and Ternan, and nitrogen (N 2 ) by Casati et al (1)(2)(3)(4)(5)(6). Recently, Angelo et al have demonstrated that a H 2 pump can be used to purify inert gases where H 2 was successfully separated from inert Helium (He) using a proton exchange membrane fuel cell system (PEMFCS) (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…This is a costly process, however, due to challenges with liquefying the H 2 and the significant energy input required. A proton exchange membrane fuel cell operated as a H 2 pump was proposed as an alternative separation technology because the energy input is expected to be much lower than cryogenic distillation due to the facileness of the hydrogen oxidation reaction (HOR) and since system operating temperatures are much closer to ambient (7,8). Electrolytic operation was selected over galvanic operation because the He purity specifications subsequent to separation require ≤ 50 parts per million (ppm) of impurities and operating a fuel cell galvanically with air as an oxidant would result in cross-over of additional contaminants such as N 2 (7,8).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations